Effects of the adding of phenolic compounds on coating pickup and oil absorption of wheat flour based batters - Hamarashid, Shokhan Hidayat (Sulaimani Journal for Pure and Applied Sciences, 2018)
The effect of addition of different phenolic compounds including tannic acid, green tea extract containing 40% EGCG (epigallocatechin gallate) and onion extract including 20% quercetin, to batter formulations on the properties of deep-fat fried potato strips were evaluated. In the beginning, coating pick up of batter formulations were done before deep fat frying. Then, moisture content of samples after frying was found. Finally, the oil content of samples was determined after the frying process and drying. The deep fat frying was processed at 180°C. Green tea extract, and onion extract had no significant influence on moisture content in potato strips. On the contrary, the battered potato strips containing tannic acid had the lowest moisture content and differed significantly from the control. The lowest oil absorption was found in tannic acid batter coated potato strips, and the greatest in green tea extract batter coated potato strips but there was no significant different. Using the phenolic compounds in batter did not significantly (p>0.05) affect the coating pickup. The best result was obtained for the tannic acid batter because it had the highest batter pick up 46 % and the lowest oil absorbed by 36% compared to the other samples.
Keywords: Phenolic compound; Deep fat frying Potato strips; Batter; Pickup